Community-Based Hypertension Management: Qualitative Study - Marni, Marni; Firdaus, Insanul; Husna, Putri Halimu; Soares, Domingos (International Journal of Qualitative Research, 2025)
Hypertension is a global problem that causes morbidity and mortality due to cardiovascular disease, which is a burden on public health. Community-based hypertension management can improve treatment adherence, reduce the level of complications, and improve the quality of life of patients. The role of community empowerment in hypertension management. Qualitative research design to examine hypertension management carried out by the community, starting from preventive, promotive, curative, and rehabilitative actions in Sukoharjo, Central Java, Indonesia. The sampling technique was purposive sampling. Informants in this study were the Village Head, village midwife, elderly posyandu cadres, Family Empowerment and Welfare, Ward Head, Neighbourhood heads, and hypertension patients.  The instruments used were interview guidelines containing 7 themes and 20 questions. Data analysis techniques included data reduction, reliability testing, and validation of research results. Hypertension management in Ngasinan Village is a routine health check, health education to behave in a healthy way and obey the instructions of health workers, routine activities such as exercise and daily activities, eating a balanced diet, reducing salt, encouraging people to get enough rest especially at night, and stress management.